The History of Postmodernism and Its Impact on Muslim Lifestyle in Malaysia - Ali @ Mat Zin, Aizan (Journal of Al-Tamaddun, 2023)
This article aims to explore the history of postmodernism and its impact on Muslim lifestyles in Malaysia. The emergence of postmodernism is inevitable in the Muslim world due to daily interaction among cultures, religions, and ideologies through various mediums of communication. The notions of scepticism, subjectivism or relativism, and suspicion of reason nurture postmodernist way of thinking and reasoning. Then, it jeopardises the absolute sources of the Islamic way of life specifically the Quran and Hadith. One pertinent question is how does postmodernism affect the lifestyle of Muslims? Primary and secondary data are needed to be collected to answer the question and achieve the aims of this article. Thus, methods of data collection were documentation on the history of postmodernism, and observation on social media regarding the lifestyle of Muslims in Malaysia. The collected data were analysed using comparative, deductive, and inductive analyses. Findings exhibit that the system of secular education and social media exposed Muslim society in Malaysia to the postmodernism lifestyle that jeopardised Islamic teaching. Modern lifestyle demands Muslim society to discard traditional ways of thinking based on religion, and nurture stressful minds and soul. In conclusion, empowering the Islamic education in promoting an Islamic lifestyle is pivotal to nurturing healthy mind and soul in the postmodernism era.